2D Ising-Heisenberg model with quartic interaction - Valverde, J.S. (Вопросы атомной науки и техники, 2012)
We propose a two-dimensional spin-1/2 Ising-Heisenberg model with quartic interaction. In this sense the phase diagram for the model at zero temperature is studied, obtaining four different configurations for the unitary cell. It should be observed that using the rotation and spin inversion symmetry we have only three spin configurations that are relevant. In addition, the model under consideration will be straightforwardly mapped to the exactly solved eight-vertex model and the conditions for obtaining an exact solution will be investigated. The analysis was performed for two different conditions, namely, where the free fermion condition (FFC) and \ the symmetrical eight-vertex condition (SEVC) are satisfied. Предлагается двумерная модель Ising-Heisenberg со спином 1/2 и с четверным взаимодействием. Анализируется фазовая диаграмма для модели при нулевой температуре, и получены четыре различных конфигурации для унитарной ячейки. Отмечается, что при учете симметрии вращения и инверсии спина имеются только три конфигурации спина, имеющие смысл. Кроме того, рассматриваемая модель прямо отображается на точно решаемую модель с восемью вершинами, и условия получения точного решения исследованы. Анализ был сделан для двух различных условий, а именно, для случая свободных фермионов (FFC) и случая восьми симметричных вершин (SEVC). Пропонується двовимірна модель Іsіng-Heіsenberg зі спіном 1/2 і із четверною взаємодією. Аналізується фазова діаграма для моделі при нульовій температурі, й отримані чотири різних конфігурації для унітарної комірки. Відзначається, що при обліку симетрії обертання й інверсії спіна є тільки три конфігурації спіна, які мають сенс. Крім того, розглянута модель прямо відображається на точно розв'язувану модель із вісьма вершинами. Умови одержання точного рішення досліджені. Аналіз був зроблений для двох різних умов, а саме, для случаю вільних ферміонів (FFC) і случаю восьми симетричних вершин (SEVC)